2010
DOI: 10.1159/000268587
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Hepatocellular Adenoma in the Netherlands: Similarities and Differences

Abstract: Background: The diagnosis of hepatocellular adenoma (HA) has a great impact on the lives of young women and may pose clinical dilemmas to the clinician since there are no standardized protocols to follow. We aimed to establish expert opinions on diagnosis and treatment of HA by collecting data from a nationwide questionnaire in the Netherlands. Methods: A questionnaire was sent to 20 Dutch hospitals known to offer hepatologic and surgical experience on liver tumours. Results: 17 hospitals (85%) responded to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 50 publications
0
39
0
Order By: Relevance
“…[1][2][3][4][5] Molecular studies have allowed the distinction of FNH from HCA, confirming that FNH lesions are polyclonal with b-catenin activation without mutation. 6 In addition, FNH lesions exhibit a particular glutamine synthetase (GS) staining in a characteristic "map-like" pattern but do not express inflammatory proteins such as serum amyloid A (SAA) or C reactive protein (CRP) or show aberrant b-catenin nuclear staining.…”
mentioning
confidence: 91%
“…[1][2][3][4][5] Molecular studies have allowed the distinction of FNH from HCA, confirming that FNH lesions are polyclonal with b-catenin activation without mutation. 6 In addition, FNH lesions exhibit a particular glutamine synthetase (GS) staining in a characteristic "map-like" pattern but do not express inflammatory proteins such as serum amyloid A (SAA) or C reactive protein (CRP) or show aberrant b-catenin nuclear staining.…”
mentioning
confidence: 91%
“…Clinical observation is indicated in small adenomas less than 4 cm in diameter and for lesions that show a regression after stopping oral contraceptives (OC). Surgical resection should be taken into consideration in cases in which the risk of complication (bleeding and malignant transformation) is increased, in female patients with a wish for pregnancy with HA ≥ 5 cm, in post-menopausal women with HA > 5 cm after 6 mo of stop OC and in males regardless of HA size due to the high risk of β-catenin mutation [9,14] . It is more controversial the management of patients with multiple HA.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is also indicated if there is diagnostic doubt e.g. whether a tumor is malignant [18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…Most experts advocate that women with HCA should not get pregnant or advise surgical resection before pregnancy [2,18]. Cobey et al reported a maternal and fetal mortality risk of ruptured HCA during pregnancy of 44% and 38%, respectively [20].…”
Section: Introductionmentioning
confidence: 99%